Advantages of Aluminium Hydroxide Adsorbed Combined Diphtheria, Tetanus, and Pertussis Vaccines for the Immunization of Infants. Issue 5645 (15th March 1969) - Butler, N. R.; Voyce, M. A.; Burland, W. L.; Hilton, Marjorie L.
Abstract : Three combined triple antigen vaccines were used to inoculate infants receiving primary immunization at 3 to 6 months of age. Laboratory potency and toxicity tests and clinical evaluation again showed that the mouse weight gain test is able to predict which vaccines will give reactions in children. The addition of aluminium hydroxide to the vaccine both increased potency and reduced the tendency to cause reactions. Assays on sera showed that almost all children produced agglutinins to Bordetella pertussis types 1, 2, and 3 when the vaccine contained aluminium hydroxide.